Laboratory Utilization and Analytical Validation of Fecal Electrolyte Tests. (1st May 2017) - Parakh, Rugvedita; Greene, Dina N; Mathias, Patrick C; Block, Darci R; Ranjitkar, Pratistha
Abstract: Background: Chronic diarrhea can be categorized as fatty, watery, or inflammatory. Watery diarrhea is further divided into secretory or osmotic types and can be differentiated by measuring fecal electrolytes and osmotic gap. However, with widespread use of endoscopy, it is unclear if these measurements are being used clinically. Furthermore, because stool is not a validated specimen type for Food and Drug Administration–approved electrolyte assays, utilization is a practical concern for laboratories before analytical validation. Here, we determined the clinical utility and validated the performance characteristics of stool electrolytes on the Beckman Coulter AU680. Methods: Historical results and literature review were used to determine the clinically relevant ranges for stool electrolytes (Na +, Cl −, K +, phosphate, and Mg 2+ ). Additionally, medical chart review was performed (n = 44 patients) on results to evaluate their clinical utility in chronic diarrhea work-up. Linearity, precision, and stability studies were performed on the AU680. Accuracy was evaluated by comparing results to the Roche Cobas 6000 c501. Results: For all cases, stool electrolytes and osmotic gap proved valuable in chronic diarrhea work-up. The imprecision of the assays ranged from 0% to 5.9%. All assays were found to be linear within the instrument's analytical measurement range with appropriate slopes and intercepts. The bias between the AU680 and the Roche c501 ranged from −0.48 to 2.39 (mmol/L or mg/dL). Na +, Cl −, and K + were stable refrigerated for 5 days and up to 1 freeze-thaw cycle. Phosphate and Mg 2+ were stable refrigerated for 48 h, but unstable to freeze-thaw cycles. Conclusions: Stool osmotic gap is valuable for evaluating chronic diarrhea and can be calculated using electrolyte concentrations measured on the AU680.